Atmospheric Rivers in Africa Observed with GNSS-RO and Reanalysis Data - Linda Martina Maier; Bahareh Rahimi; Ulrich Foelsche (Remote Sensing)
Atmospheric Rivers (ARs) transport significant amounts of moisture and cause extreme precipitation events, yet their behavior over Africa is not well understood. This study addresses this gap by analyzing the occurrence, seasonal variability, and spatial dynamics of ARs across the continent from 2009 to 2019. Utilizing ERA5 reanalysis data, Global Navigation Satellite Systems Radio Occultation (GNSS RO) measurements, and the Image-Processing-based Atmospheric River Tracking (IPART) method, distinct seasonal AR patterns are identified. Southern Africa experiences peak activity during austral summer, while AR occurrence in Northern Africa peaks in boreal winter and spring, aligning with regional rainy seasons. Moisture sources include the Atlantic Ocean, the Arabian Sea, and the Red Sea. A comparison of ERA5 Integrated Water Vapor (IWV) estimates with high-resolution GNSS RO data shows that both datasets effectively capture broad-scale moisture patterns. However, ERA5 consistently delivers higher IWV values compared to GNSS RO, which is likely due to underrepresentation of GNSS RO IWV values, since profiles generally do not reach all the way down to the surface—but also due to an overrepresentation of humidity in the ERA5 reanalyses. Understanding AR dynamics in Africa is essential to improve climate resilience, water management and understanding extreme precipitation events.